Interventions to mitigate the impact of COVID-19 pandemic on mental health status of healthcare workers: a systematic review - Zahid, Maham; Hussain, Umar; Noreen, Shaista; Kabir, Sofia; Rehman, Khalid (Journal of the Pakistan Medical Association, 2025)
Objective: To evaluate the effectiveness of interventions in addressing the impact of coronavirus disease-2019 on the mental health status of healthcare workers. Method: The systematic review was conducted from January to August 2023 in line with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines, and comprised search on Medical Literature Analysis and Retrieval System Online, Excerpta Medica database, Allied and Complementary Medicine Database Cumulative Index to Nursing and Allied Health Literature and Cochrane Central Register of Controlled Trials databases for relevant randomised clinical trials published till January 25, 2022, focussing on assessing the effectiveness of interventions addressing the impact of coronavirus disease-2019 on healthcare workers. The risk of bias of the studies was assessed using the revised Cochrane risk of bias tool for randomised clinical trials RoB 2.0. Results: There were 17 randomised clinical trials with 4,511 participants. Overall findings showed that mindfulness-based interventions, yoga/music, music therapy/meditation, psychological interventions, creative arts therapy, and acupuncture could be effective in improving mental health outcomes for healthcare workers dealing with coronavirus disease-2019 patients. Pharmacological interventions and transcendental meditation may not be as effective. Conclusion: Implementing non-pharmacological interventions to support the mental health of healthcare workers during times of crisis could be a positive approach. Key Words: COVID-19, Mental health, Anxiety, Depression, Post-traumatic distress syndrome.